2010
DOI: 10.1002/adma.200903934
|View full text |Cite
|
Sign up to set email alerts
|

Thiolate‐Protected Aun Nanoclusters as Catalysts for Selective Oxidation and Hydrogenation Processes

Abstract: Thiolate‐protected Aun clusters are exploited as homogeneous and supported catalysts for two chemical processes: i) the selective oxidation of styrene by O2 to benzaldehyde and ii) the chemoselective hydrogenation of α,β‐unsaturated ketone to α,β‐unsaturated alcohol. The results demonstrate that a quantum‐size effect in Aun clusters plays a critical role in their catalysis. This work highlights the importance of pursuing quantum‐sized gold clusters for catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
213
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(217 citation statements)
references
References 35 publications
1
213
2
1
Order By: Relevance
“…Aikens and co-workers have theoretically studied this process by examining the electron and hydride addition to gold(I)-thiolate oligomers (Au N (SR) N , N ¼ 3-7). 153 The addition of a hydride ion to gold(I)-thiolate oligomers led to the production of free thiols and Au(0)-containing chain-like oligomers, which is considered as a possible intermediate for the [149][150][151] Few theoretical studies have been reported on the origin of catalytic activity and the structure-activity relationship of these clusters. With more atomic structures of thiolate-protected gold clusters being determined, a better understanding of the structure-activity selectivity relationship is expected in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Aikens and co-workers have theoretically studied this process by examining the electron and hydride addition to gold(I)-thiolate oligomers (Au N (SR) N , N ¼ 3-7). 153 The addition of a hydride ion to gold(I)-thiolate oligomers led to the production of free thiols and Au(0)-containing chain-like oligomers, which is considered as a possible intermediate for the [149][150][151] Few theoretical studies have been reported on the origin of catalytic activity and the structure-activity relationship of these clusters. With more atomic structures of thiolate-protected gold clusters being determined, a better understanding of the structure-activity selectivity relationship is expected in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster 3 ( Figure S5D in the Supporting Information) does not show significant peaks in both negative and positive modes. For cluster 2, the spectrum shows ( Figure 2 and Figure S5C in the Supporting Information) a molecular ion peak at m/z 2839 along with some fragments at m/z 2604 and 2204, which have been assigned as [Ag 5 10 ] − , respectively. The fragments are due to (SePh+Ph) and Ag 2 Pd(SePh) 2 losses, respectively ( Figure 2).…”
Section: Section: Physical Processes In Nanomaterials and Nanostructuresmentioning
confidence: 99%
“…MS/MS of the fragment at m/z 2604 was also studied ( Figure S6 in the Supporting Information), and for this case, successive ligand losses were seen and the metal core remains intact throughout. MS 2 of [Ag 5 Pd 4 (SePh) 10 Se] − produces two new peaks due to consecutive losses of two units of (SeR+R), part of the ligand. Mass difference for the fragments obtained from MS 3 of the peak at m/z 2374 corresponds to the losses of two units of selenium and one R. Similar trends have been observed for MS 4 (11.7%); abundances are given as percentages).…”
Section: Section: Physical Processes In Nanomaterials and Nanostructuresmentioning
confidence: 99%
“…Recently, Jin et al reported the Au n (SR) m nanocluster catalysts for selective oxidation of styrene using three robust supersmall Au n nanoclusters, including Au 25 (1.0 nm), Au 38 (1.3 nm) and Au 144 (1.6 nm) [23,26]. The catalytic activity of Au n nanocluster catalysts exhibits a strong dependence on size (n); the smaller Au n (SR) m nanoclusters give rise to a much higher catalytic activity.…”
Section: Catalytic Performance Of Atomically Precise Gold Nanoclutersmentioning
confidence: 99%
“…Overall, the non-metallic behavior of Au n in both size regimes is particularly important for nanocatalysis. More importantly, on the basis of their atom packing structures and unique electronic properties, one could indeed study a precise correlation of structural properties with catalytic properties, identify the catalytically active sites on the gold particle and unravel the nature of gold catalysis [21][22][23][24][25][26][27]. This has long been an important task in nanocatalysis [28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%